The elephant’s Achilles’ heel: a case report of acute obstruction of frozen elephant trunk after proximal aortic dissection repair - Nienaber, Stephan; Yuan, Xun; Price, Susanna; Rosendahl, Ulrich; Nienaber, Christoph A (European heart journal : case reports, 2024)
Abstract Background The frozen elephant trunk (FET) technique as a hybrid combining surgical and endovascular repair is an emerging concept to treat complex aortic dissection. Early experience showed technical feasibility and promising clinical outcomes. However, unsuspected complications still arise. Case summary A 25-year-old male presented to the emergency department with a 2-day history of chest pain. After exclusion of acute coronary syndrome, a computed tomography angiography (CTA) revealed Type A (DeBakey Type I) aortic dissection. The patient underwent median stenotomy for complete replacement of the ascending aorta, the aortic arch, and FET. Early after rewarming, the patient became unstable due to severe left ventricular dysfunction. Soon veno-arterial extracorporal membrane oxygenation (VA-ECMO) was required for circulatory support. The cause of deterioration remained unclear until repeated CTA showed acute obstruction of the FET. Invasive exploration confirmed a trans-FET gradient of 100 mmHg, successfully managed by repeated balloon inflation with resolution of both obstruction and gradient. The patient recovered completely without any sequela. Discussion While the mechanism of acute obstruction after FET remains subject to speculation, the rescue intervention of ballooning the obliteration on VA-ECMO was life-saving. Intraoperative ultrasound and videoscopic inspection may be instrumental before chest closure to avoid such critical events.